La cortesía española frente a la cortesía inglesa. Estudio pragmalingüístico de las exhortaciones impositivas. - Ballesteros Martín, Francisco (Estudios Ingleses de la Universidad Complutense, 2001)
This article tries to prove that it is not objectively verifiable to catalogue the native speakers of a specific society as more polite than the speakers of another. The existing topics tend to stereotype Spanish speakers as less polite than the British. This typification is not correct and I shall try to demonstrate that it probably stems from the fact that Spanish speakers use positive politeness strategies in a significantly higher proportion than British speakers, who show an intrinsic tendency to negative politeness strategies in the same situational contexts. This empirical study is based on the comparison of the realization patterns preferred by native speakers of both nationalities when uttering two kinds of impositive acts: requests and commands. The results also prove another significant variation in the requesting behaviour of the surveyed individuals: Spaniards prefer syntactically more direct strategies in a frequency ratio which sounds too impositive to the British, who rather use more routinized conventionally indirect types. As a conclusion it can be claimed that these results, after using the non-parametric chi-square test, prove that the nature of the analyzed requestive acts is clearly culture-specific, i.e. part of an emic system, which characterizes the speakers of each society and which usually produces cross-cultural transfers that we all could advisably try to know and avoid when speaking a foreign language. 1.